WANPRESTASI PEMESAN DALAM PEMBAYARAN PEMBUATAN BANNER PADA PENGUSAHA CV. BAKULAPURA PRODUCTION DI KECAMATAN SUNGAI RAYA - NIM. A1011181134, RINDU SAFITRI SUYITNO (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstrac CV. Bakulapura Production is a printing company that provides services for making banners, printing yasin books, invitations, stickers, making placards and so on. However, in this printing service business, obstacles often occur. Where the obstacle was caused by the large number of banner customers who did not pay on time according to what was agreed. Agreement between CV Entrepreneurs. Bakulapura Production by ordering banners as service users which in civil law are included in the type of agreement to perform certain services. Agreement between CV. Bakulpura Production to the banner orderer is carried out verbally (not in writing) even though it is carried out verbally but the binding force is the same as an agreement made in writing and the agreement creates rights and obligations for the parties, because the agreement has fulfilled the legal requirements of the agreement stipulated in Article 1320 The Civil Code, which prohibits those who bind themselves, the ability to make or enter into an agreement, a certain matter and a lawful cause. This thesis contains a problem formulation, namely: